Modulation of sphingosine‐1‐phosphate and apolipoprotein M levels in the plasma, liver and kidneys in streptozotocin‐induced diabetic mice. Issue 6 (21st April 2014) - Nojiri, Takahiro; Kurano, Makoto; Tokuhara, Yasunori; Ohkubo, Shigeo; Hara, Masumi; Ikeda, Hitoshi; Tsukamoto, Kazuhisa; Yatomi, Yutaka
Abstract Aims/Introduction Sphingosine‐1‐phosphate (S1P), a multifunctional bioactive lipid mediator, is involved in various diseases. Apolipoprotein M (ApoM) carries S1P on high‐density lipoprotein and modulates S1P metabolism to increase the total S1P mass in the body. Both S1P and ApoM are involved in diabetes. Materials and Methods The present study examined the modulation of S1P and ApoM levels in the plasma, liver and kidneys in streptozotocin‐induced diabetes (STZ) mice, and the effects of insulin on the S1P and ApoM levels in the plasma and liver in STZ mice and normal mice. We also examined the effects of insulin and glucose on the ApoM levels in HepG2 cells. Results In STZ mice, both the plasma S1P and ApoM levels were higher than those in control mice. The hepatic S1P and ApoM contents were also elevated. The hepatic S1P and ApoM contents were reduced by insulin treatment, whereas high‐dose insulin decreased the plasma S1P and ApoM levels. In mice without streptozotocin treatment, the administration of insulin decreased the plasma S1P and ApoM levels, and the hepatic content of ApoM, whereas the hepatic level of S1P was not altered. Treatment with insulin and incubation under a low glucose level decreased the ApoM levels in HepG2 cells. Regarding the kidney, the renal levels of S1P and ApoM were increased in STZ mice, and insulin treatment partially restored this increment. Conclusions In STZ mice, the levels of S1P and ApoM in the plasma, liver, and kidneys were increased. Insulin treatment somehow reversed this modulation in STZ mice.